Oak (Quercus robur) Associated Endophytic Paenibacillus sp. Promotes Poplar (Populus spp.) Root Growth In Vitro - Dorotėja Vaitiekūnaitė; Sigutė Kuusienė; Emilija Beniušytė (Microorganisms, 2021)
Soil fertilization is necessary for high-demand crop production in agriculture and forestry. Our current dependence on chemical fertilizers has significant harmful side effects. Biofertilization using microorganisms is a sustainable way to limit the need for chemical fertilizers in various enterprises. Most plant endophytic bacteria have thus far been unstudied for their plant growth promoting potential and hence present a novel niche for new biofertilizer strains. We isolated English oak (Quercus robur) endophytic bacteria and tested them for plant growth promoting traits (PGPTs) such as nitrogen fixation, phosphate mineralization/solubilization, siderophore and indole-3-acetic acid (IAA) production. We also investigated the effect the selected isolate had on poplar (Populus spp.) microshoot vegetative growth parameters in vitro. In total 48 bacterial strains were isolated, attributed to Bacillus, Delftia, Paenibacillus, Pantoea and Pseudomonas genera. All the isolates displayed at least three PGPTs, with 39.6% of the isolates displaying all five (all were Pseudomonas spp.) and 18.75% displaying four. Based on relative abundance, Paenibacillus sp. isolate was selected for the poplar microshoot inoculation study. The isolate had a significant positive effect on poplar microshoot root growth and development. Two tested poplar genotypes both had increased lateral root number and density, fresh and dry root biomass. Furthermore, one genotype had increased length and number of adventitious roots as well as a decrease in fresh aboveground biomass. The root enhancement was attributed to IAA production. We propose this isolate for further studies as a potential biofertilizer.